Discussion about Testing Scheme of Intelligent Medical Devices - Nan ZHANG; Jing LI; Jie ZHANG; Jiong YANG; Zhengbo ZHANG; Kunlun HE (Zhongguo yiliao qixie zazhi)
Intelligent medical devices are flourishing with the deep integration of modern information and artificial intelligence technologies into healthcare. Testing is an important means of performance evaluation and quality control for intelligent medical devices. Compared with traditional medical devices, the testing methods and technologies of intelligent medical devices are still immature, and need active research to promote the progress in this area. Intelligent medical devices are classified according to their characteristics as artificial intelligence medical devices in the form of software and medical robots based on a general discussion of their development. The medical-device Internet of Things (IoT) system has also been included due to its close relation to the construction of smart hospitals. For each type of intelligent medical device, testing indexes and testing plans are discussed. It is suggested that specific test rules should be further developed for various specific devices. Besides, the evaluation method of complex intelligent systems should be introduced and real-world data should be used for evaluation. This paper aims to accelerate the development of intelligent medical device testing, laying the foundation for quality control and performance evaluation of intelligent medical devices.